2011
DOI: 10.1039/c1ee01203g
|View full text |Cite
|
Sign up to set email alerts
|

Proton exchange membrane electrolysis sustained by water vapor

Abstract: The current-voltage characteristics of a proton exchange membrane (PEM) electrolyzer constructed with an IrRuO x water oxidation catalyst and a Pt black water reduction catalyst, under operation with water vapor from a humidified carrier gas, have been investigated as a function of the gas flow rate, the relative humidity, and the presence of oxygen. The performance of the system with water vapor was also compared to the performance when the device was immersed in liquid water. With a humidified Ar(g) input st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 19 publications
3
105
0
3
Order By: Relevance
“…[35b] The electrolysis of water using commercially available membrane-electrode assemblies with a water-vapor feed has demonstrated operating current densities on the order of tens of mA cm À2 , which is sufficient for the operation of a broad range of solar-driven water-splitting devices. [73] Reduced current density and cell failure using vapor feed are often caused by limitations in the mass transport of the reactant water and dehydration of the membrane electrolyte resulting in increased ohmic losses. A light-driven demonstration system was reported that used a membrane-electrode assembly with photoactive TiO 2 nanoparticles incorporated into the membrane layer (Figure 4 d1).…”
Section: Vapor-feed Designmentioning
confidence: 99%
“…[35b] The electrolysis of water using commercially available membrane-electrode assemblies with a water-vapor feed has demonstrated operating current densities on the order of tens of mA cm À2 , which is sufficient for the operation of a broad range of solar-driven water-splitting devices. [73] Reduced current density and cell failure using vapor feed are often caused by limitations in the mass transport of the reactant water and dehydration of the membrane electrolyte resulting in increased ohmic losses. A light-driven demonstration system was reported that used a membrane-electrode assembly with photoactive TiO 2 nanoparticles incorporated into the membrane layer (Figure 4 d1).…”
Section: Vapor-feed Designmentioning
confidence: 99%
“…They noted the important effect of relative humidity on performance, whereas absolute humidity has less importance. Spurgeon and Lewis showed that a vapor phase electrolyzer can reach a current density of 20 mA cm À2 , congruent with current densities of PV and PEC devices, but found that performance dropped steeply at reduced relative humidity [21]. Their work suggests that ion exchange membranes can be operated in vapor phase, albeit at lower current densities than usually encountered in electrolyzers.…”
Section: Air-based Solar Hydrogen Productionmentioning
confidence: 96%
“…Although water concentration in air is rather low, the moderate current density encountered in solar H 2 devices implies they should be able to extract sufficient water from it. Some authors have suggested the use of air as a water feedstock recently [21,68,69]. They noted the important effect of relative humidity on performance, whereas absolute humidity has less importance.…”
Section: Air-based Solar Hydrogen Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…These devices are in the early stage of development, but guidelines for their fabrications have been drawn from modeling studies (58,115), and experimental operation of MEA electrolyzers on the vapor phase has been demonstrated (116). Also, proper thermal management in devices can allow systems to operate continuously at higher levels of efficiency.…”
Section: Figurementioning
confidence: 99%